2017
DOI: 10.1016/j.jaad.2017.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake and risk of rosacea in US women

Abstract: Background The epidemiologic association between alcohol and rosacea is unclear and inconsistent based on prior cross-sectional or case-control studies. Objective We conducted a cohort study to determine the association between alcohol intake and the risk of incident rosacea. Methods A total of 82,737 women were included from the Nurses’ Health Study II (1991–2005). Information on alcohol intake was collected every four years during follow-up. Information on history of clinician-diagnosed rosacea and year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
6
29
0
3
Order By: Relevance
“…Other studies have also concluded that the average TC and LDL levels of tumor patients were lower than the control group . Previous studies have reported that dyslipidemia is significantly associated with rosacea . In the logistic regression model of this study, high LDL levels (OR = 2.22) and low HDL levels (OR = 2.37) in breast cancer patients with rosacea were significantly higher than rosacea‐free patients, which may be related to inflammation.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…Other studies have also concluded that the average TC and LDL levels of tumor patients were lower than the control group . Previous studies have reported that dyslipidemia is significantly associated with rosacea . In the logistic regression model of this study, high LDL levels (OR = 2.22) and low HDL levels (OR = 2.37) in breast cancer patients with rosacea were significantly higher than rosacea‐free patients, which may be related to inflammation.…”
Section: Discussionsupporting
confidence: 42%
“…54 Previous studies have reported that dyslipidemia is significantly associated with rosacea. 5,55 In the logistic regression model of this study, high LDL levels (OR = 2.22) and low HDL levels (OR = 2.37) in breast cancer patients with rosacea were significantly higher than rosacea-free patients, which may be related to inflammation. Low-grade chronic inflammation in patients alters lipid metabolism, and affects lipoprotein synthesis and metastasis.…”
Section: Discussionmentioning
confidence: 71%
“…Naldi et al 12 found that less carbohydrate and fatty food composition were beneficial to psoriatic patients. Abram et al 16 demonstrated that coffee intake and alcohol consumption were not related to rosacea, while in the surveys of Duman and Ersoy Evans 6 and Li et al 17 they found that alcohol consumption was more prevalent in rosacea patients. By contrast, the consumption of rice, coffee and fermented food were beneficial to patients with atopic dermatitis.…”
Section: Introductionmentioning
confidence: 98%
“…Previous researches were restricted to investigating limited dietary factors such as coffee and alcohol and their effects on the skin of patients with rosacea. Abram et al 16 demonstrated that coffee intake and alcohol consumption were not related to rosacea, while in the surveys of Duman and Ersoy Evans 6 and Li et al 17 they found that alcohol consumption was more prevalent in rosacea patients. Additionally, some of these studies were merely based on a small population.…”
Section: Introductionmentioning
confidence: 98%
“…En cuanto a las preferencias de consumo en la dieta, Alinia y cols (9) demostraron que estos desencadenantes incluyen comida picante, bebidas calientes y tabaco; y aunque el alcohol es un desencadenante precisaron que la asociación entre el consumo de alcohol y el desarrollo de la severidad de la rosácea no está del todo claro, como también se observó en un estudio en Asturias (10) encontrándose como desencadenante al té, el café y otros; de igual modo Li (11) encontró que si hay asociación entre la rosácea y las preferencias de consumo en la dieta; sin embargo, nuestro e s t u d i o n o e n c o n t r ó a s o c i a c i ó n estadísticamente significativa entre estos factores, lo que se podría explicarse debido que al ser la población estudiada usuaria del comedor universitario, tienen una dieta con mayor equilibrio entre sus componentes, por lo que en esta población en especial no sería un factor de riesgo importante.…”
Section: Análisis Estadísticounclassified